Transformasi Manajemen Pakan: Pemberdayaan Peternak dalam Optimalisasi Silase untuk Ternak Sapi Potong - Bonewati, Yulia Irwina; Herni; Maryam; Farid, Muhammad; Nurdaida; Puspitasari, Ita (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The availability of high-quality feed is a crucial factor in supporting the productivity of beef cattle especially in areas with limited resources and seasonal fluctuations. Particularly during the dry season, the availability of green forage becomes limited and difficult to obtain. This community service activity aims to assist farmers in utilizing locally available materials as economical, nutritious, and sustainable alternative feed. The methods employed include extension, technical training, and hands-on practice in making silage from local ingredients such as Pennisetum purpureum, rice bran, and molasses. The activity was conducted at the Agricultural Extension Center in Waempubbu Village, Amali Subdistrict, Bone Regency, involving 38 livestock farmers representing farmer groups from across Amali Subdistrict. The results of the mentoring program showed an increase in farmers' knowledge and skills in formulating alternative feed. This activity is expected to strengthen feed security at the farmer level and serve as a sustainable empowerment model within smallholder livestock systems.